Forecasting South China Sea Monsoon Onset Using Insight From Theory - Ruth Geen (Geophysical Research Letters)
Abstract Monsoon onset over the South China Sea occurs in April–May, marking the start of the wet season over East Asia. Skillful prediction of onset timing remains an open challenge. Recently, theoretical studies using idealized models have revealed feedbacks at work during the seasonal transitions of the Hadley cells and have shown that these are relevant to monsoon onset over Asia. Here, I hypothesize that monsoon onset occurs earlier in years when the atmosphere over the South China Sea is already in a state where these feedbacks are more easily triggered. I find that local anomalies in lower‐level moist static energy in the preceding January–March are well correlated with South China Sea Monsoon onset timing. This relationship remains relatively consistent on decadal timescales, while correlations with other teleconnections vary, and is used to develop a simple forecast model for onset timing that shows skill competitive with that of more complex models.